8a-2b+4-3b+a-3=

Simple and best practice solution for 8a-2b+4-3b+a-3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8a-2b+4-3b+a-3= equation:


Simplifying
8a + -2b + 4 + -3b + a + -3 = 0

Reorder the terms:
4 + -3 + 8a + a + -2b + -3b = 0

Combine like terms: 4 + -3 = 1
1 + 8a + a + -2b + -3b = 0

Combine like terms: 8a + a = 9a
1 + 9a + -2b + -3b = 0

Combine like terms: -2b + -3b = -5b
1 + 9a + -5b = 0

Solving
1 + 9a + -5b = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + 9a + -1 + -5b = 0 + -1

Reorder the terms:
1 + -1 + 9a + -5b = 0 + -1

Combine like terms: 1 + -1 = 0
0 + 9a + -5b = 0 + -1
9a + -5b = 0 + -1

Combine like terms: 0 + -1 = -1
9a + -5b = -1

Add '5b' to each side of the equation.
9a + -5b + 5b = -1 + 5b

Combine like terms: -5b + 5b = 0
9a + 0 = -1 + 5b
9a = -1 + 5b

Divide each side by '9'.
a = -0.1111111111 + 0.5555555556b

Simplifying
a = -0.1111111111 + 0.5555555556b

See similar equations:

| y-9=0.3(x+2) | | 4cos^2x-4cosx-3=3 | | -9x(x+6)=3(x+18) | | a+c=b+c | | -10n+10=-12n | | y-9=0.3(x+9) | | y-7=-3(x-1) | | 3x(4x-8)(x+5)=0 | | (2xlnx-x)/lnx^2=0 | | 13x+4(2x-1)=5(x+2) | | 3a+6b-5a+2b= | | 9b-3b+11=23 | | 8/360=40/x | | 10(x+4)-9(x-3)=8 | | 3(x-7)=x+13 | | 2.27-s/4=2 | | 3(x-7)=x+133 | | 4=2y-3 | | -21x-7=-x+53 | | 8a+2=6a+4 | | 3m+1=m+1 | | X-3=-12x+10 | | x^2+y^2+x+y-96=0 | | 36=-0.5x^2+108 | | 2y+7=-2y-1 | | 4/9/x=12 | | (2x+3y-4)dx+(-4x+y+1)dx=0 | | 7x-3.5=-4x-3.2 | | 2-2x=6-1x | | 5/9÷15/36 | | x^5-125x^3+484x=0 | | 20-8.50= |

Equations solver categories